Biosensors paving the way to understanding the interaction between cadmium and the estrogen receptor alpha. - Peter Fechner (Public Library of Science (PLoS), 2011)
Cadmium is a toxic heavy metal ubiquitously present in the environment and subsequently in the human diet. Cadmium has been proposed to disrupt the endocrine system, targeting in particular the estrogen signaling pathway already at environmentally relevant concentrations. Thus far, the reports on the binding affinity of cadmium towards human estrogen receptor alpha (hERα) have been contradicting, as have been the reports on the in vivo estrogenicity of cadmium. Hence, the mode of interaction between cadmium and the receptor remains unclear. Here, we investigated the interaction between cadmium and hERα on a molecular level by applying a novel, label-free biosensor technique based on reflectometric interference spectroscopy (RIfS). We studied the binding of cadmium to hERα, and the conformation of the receptor following cadmium treatment. Our data reveals that cadmium interacts with the ligand binding domain (LBD) of the ERα and affects the conformation of the receptor. However, the binding event, as well as the induced conformation change, greatly depends on the accessibility of the cysteine tails in the LBD. As the LBD cysteine residues have been reported as targets of post-translational modifications in vivo, we present a hypothesis according to which different cellular pools of ERα respond to cadmium differently. Our proposed theory could help to explain some of the previously contradicting results regarding estrogen-like activity of cadmium.